Development of the Northern Sea Route as a space for entrepreneurship and trade - A. M. Novozhilov (Путеводитель предпринимателя, 2024)
Since ancient times, travelers, discoverers, entrepreneurs and traders have sought to find the most rational route from one area of the globe to another. Reducing distances in space means reducing commercial transactions in time, accelerating trade turnover, saving money, and increasing profits. Such circumstances have long stimulated economic participants to search for new transport routes for trade communications. They were looking for the shortest and most convenient routes from European countries to the riches of the countries of the East, India and China. Land and water routes through the regions of the North were developed. The development of northern routes began a long time ago. Already from the 6th–9th centuries, the settlement of the Eastern Slavs in northern Europe took place. From the 8th century, the Slavs began to develop the White Sea region. From the 12th century, the areas of the Kholmogory region were mentioned; Kochi Novgorodians and Pomors already walked along the western parts of the Arctic Ocean. Since the 16th century, the British and Dutch have sought to pave the way to the East through the northern seas, and trade, political and cultural ties between Russia and Western countries have been formed. Trading companies emerged; the British and Dutch, through joint–stock companies, attracted broad masses of people and their capital to colonial policy, which for a long time became the key to effective colonial activity. The Russian Empire and the young Soviet state continued to explore the Northern Sea Route.